Keberadaan Bakteri Listeria monocytogenes pada Keju Gouda Produksi Lokal dan Impor (PRESENCE OF LISTERIA MONOCYTOGENES IN LOCAL AND IMPORTED GOUDA CHEESES) - Pazra, Debby Fadhilah; Purnawarman, Trioso; Lukman, Denny Widaya (Jurnal Veteriner, 2014)
Listeria monocytogenes is included in the foodborne pathogen, which has been associated with severaloutbreaks of human listeriosis especially in high risk groups. Listeria monocytogenes could be found inGouda cheeses because of poor hygienic and sanitation practices. In addition, this bacteria could surviveduring the making of cheese and cheese ripening process. The purpose of this study was to identify thepresence of L. monocytogenes in local and imported Gouda cheeses and how the safety level of the Goudacheese against contamination of L. monocytogenes. This study used the conventional method in accordancewith the Bacteriological Analytical Manual, US Food and Drug Administration and Bergey’s Manual ofDeterminative Bacteriology to detect the presence of L. monocytogenes at 15 samples of local Gouda cheeseand 15 samples of imported Gouda cheese sold in supermarkets in Jakarta and Bogor. The results of thisstudy showed that was not found L. monocytogenes in local and imported Gouda cheese. It could be concludedthat is Gouda cheese relatively safe from L. monocytogenes and meets Indonesian National Standard.
Keywords: Local and imported Gouda cheeses, Listeria monocytogenes